(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Prodan L. А. Training the future primary school teacher by addressing materials of local history museum. The article discusses ways of successful professional training of primary school teachers in the context of addressing materials of local history museum. The author characterizes kinds of work to be done in universities’ local history museums which students accompanied by their university teachers attend. The article clarifies what tasks motivate students’ interest in local history, develop their research skills, initiative and creativity.